Collected Works of C. G. Jung, Volume 6 : Psychological Types - Jung, C. G. (Carl Gustav), 1875-1961 (Book collections on Project MUSE., 2014)
One of the most important of Jung's longer works, and probably the most famous of his books, Psychological Types appeared in German in 1921 after a ""fallow period"" of eight years during which Jung had published little. He called it ""the fruit of nearly twenty years' work in the domain of practical psychology, "" and in his autobiography he wrote: ""This work sprang originally from my need to define the ways in which my outlook differed from Freud's and Adler's. In attempting to answer this question, I came across the problem of types; for it is one's psychological type which from t.